Demulsification Kinetics of Water-in-Oil Emulsions of Ecuadorian Crude Oil: Influence of Temperature and Salinity - Jordy Sarmas-Farfan; Antonio Diaz-Barrios; Teresa E. Lehmann; Vladimir Alvarado (Energies, 2025)
This work focuses on the stability analysis of water-in-oil macroemulsions with a crude oil from the Sacha Field in Ecuador. This field is an important hydrocarbon resource in Ecuador with a typical bottom freshwater drive. The comprehensive stability analysis includes coalescence, water resolution or phase separation, and water–oil interfacial tension and interfacial dilatational viscoelastic modulus measurements over time. Two main parameters, due to their relevance, were controlled in these experiments: water salinity and temperature. The analysis reported here is the first focused on this important resource in Ecuador. Findings shed light on which mechanisms more likely control the stability of these water-in-oil macroemulsions. Results herein suggest that regardless of temperature, low-salinity water favors emulsion stability, likely due to the tendency of a stiffer interface formation at low-ionic strength, as interfacial viscoelasticity measurements show. This implies that the low-ionic strength water from the aquifer can enable the formation of stable emulsions. In contrast, water resolution depends significantly on temperature, possibly due to higher sedimentation rates. The implication is that if emulsions do not break up before cooling off, the emulsion can become more stable. Finally, analysis of the interface buildup rates could explain the observed increase in emulsion stability over time.